Managerial Competencies, Financial Management, and Level of Liquidation Practices of Secondary School Administrators - Operario, Judy (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
This study investigated the relationship of managerial competence to financial management and liquidation practices, respectively, among 48 public secondary school administrators in the schools division of Eastern Samar, Philippines. Using the researcher-developed survey instrument, the data collected were analysed using frequency count, median, and spearman rho analysis at 0.05 level of significance. Findings revealed a very high level of perceived managerial competence among the respondents. Moreover, they are practicing financial management protocols at all times, while oftentimes for liquidation protocols. Further analysis revealed no significant association among the variables, which indicates independence among them. Hence, the researcher recommends further exploration using other tools and a bigger sample size. Keywords: Managerial Competencies, Financial Management, Liquidation Practice, Public Secondary School Administrators